Phytohormones as Potential Anticancer Agents - Ashmit Gill; Somi Patranabis (International Journal for Research in Applied Sciences and Biotechnology, 2021)
The global burden of cancer is projected to have more than doubled over the next two decades, raising the prospect of a significant investment in health systems, thus posing a real medical problem. The increasing number of people with cancer highlights the need for more cancer prevention efforts. An established history exists for plant-derived compounds as effective anticancer agents. More recently, several phytohormones have been assessed for their ability to inhibit the growth and survival of human cancer cell lines. Phytohormones or plant hormones are chemical messengers responsible for harmonizing various cellular activities that revolves around growth, development, and stress-response. The aim of this literature review article is to present the current state of knowledge concerning the several naturally occurring phytohormones which have shown enormous potential in the prevention and treatment of variety of different type of cancers.